Rancang Bangun Modul Pembelajaran Bahasa Prancis Bagi Staf Tourist Information Center (TIC) DI Bandung - Tasfiyatunnisa, Salma; Siti Karimah, Iim; Mulyadi, Yadi (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2025)
Mastery of foreign languages, particularly French, plays a crucial role in supporting tourism services in Bandung. As the frontline of tourist services, the Tourist Information Center (TIC) staff are expected to communicate effectively with international visitors, including those from French-speaking countries. This study aims to design and develop an A1-level French learning module tailored to the specific needs of TIC staff in Bandung. The research employed a Research and Development (R&D) approach consisting of needs analysis, module design, expert validation, and limited trials. The participants were six TIC staff members in Bandung who had no prior formal learning experience in French. Data were collected through observation, interviews, and questionnaires, and analyzed using both quantitative and qualitative descriptive methods. The result was a contextual, practical, and applicable learning module comprising six units focused on real-life communication situations in the tourism sector. Expert validation indicated that the module was feasible with minor revisions, while the trial implementation achieved an average score of 4.46 (89.2%), categorized as “Highly Feasible.” These findings demonstrate that the A1-level French learning module is effective for self-directed learning among TIC staff and contributes to improving the quality of tourism services in Bandung.